Penguatan identitas kebangsaan di periode globalisasi: kontribusi anak muda indonesia - Syabaniyah, Fadhilah (Maliki Interdisciplinary Journal, 2026)
The study discusses the importance of strengthening national identity among Indonesian youth in the era of globalization. Globalization has brought various impacts on society, especially for young people who are closely connected to technology and social media. The easy access to foreign cultures can influence their mindset and values, potentially reducing their sense of pride in local culture. Therefore, efforts are needed to maintain and strengthen national identity so that young people continue to have a sense of nationalism and pride in Indonesian culture. This study uses a literature review method by examining various relevant sources. The results show that strengthening national identity can be achieved throught character education, preservation of local culture, proper use of the Indonesian language, and wise use of technology. Thus, young people are expected to face globalization without losing their national identity.